Management and leadership of school institutions: a qualified vision (and qualification) in the face of the great challenges of the 21st century - Campos Barrionuevo, Blas (Avances en Supervisión Educativa, 2024)
The management and leadership of educational centers are an essential factor of quality in these institutions and, therefore, of educational systems. This approach entails analyzing these figures, of a legal and socio-personal nature, in all their dimensions, in order to be aware of their relevance to respond to the great challenges of the first third of the 20th century. XXI in the educational sphere. Therefore, as school qualification variables, throughout this work, we carry out a theoretical-reflective and investigative study of them, given their structural and functional relevance in improving educational processes and teaching-learning in educational institutions. Therefore, at a sequential level we have proceeded as follows: updated vision of management in this century, comparative-evolutionary analysis of school management, analysis of the terms management and leadership in the development of management work, and management as a center qualification variable and component qualified by the educational Administration itself. The final reflections and discussions are a call to underline the importance of these educational qualification factors, which, on the other hand, must be dignified, enhanced, reinforced…, by all educational agents and, especially, by the Administration.Finally, if we have sensitized the future reader of this work about the relevance and excellence of said managerial role, as well as its permanent improvement in all its lines of action, we will have achieved the basic objective of this project.